DYNAMICS OF THE ARTISTIC CREATIVE PROCESS IN THE STORY "SUCH IS LIFE" - Isabayeva Gulhayo Farhadovna (International Journal Of Literature And Languages, 2024)
This article discusses the components and dynamics of the creative process, and the influence of the art of the word on the reader. The fact that artistic creativity is ultimately an individual phenomenon is illustrated by the example of Oʻtkir Hoshimov's story “The Affairs of the World”.